Prevalence of and prognosis for poor immunological recovery by virally suppressed and aged HIV-infected patients - Fan, Lina; Li, Penghui; Yu, Aiping; Liu, Dan; Wang, Ziyu; Wu, Yue; Zhang, Defa; Zou, Meiyin; Ma, Ping (Frontiers in Medicine, 2023)
Background Antiretroviral therapy (ART) prolongs lifespan and decreases mortality of HIV infected patients. However, many patients do not achieve optimal immune reconstitution. The influence of non-optimal immune recovery on non-AIDS related diseases is not well defined in aged HIV-infected patients receiving ART. Methods A retrospective study was conducted at Tianjin Second People’s Hospital, China to evaluate the association of an inadequate immunological response and non-AIDS diseases in HIV infected patients ≥60 years of age and virally suppressed for at least 2 years by ART. Results The study included patients (n = 666) who initiated ART between August 2009 and December 2020. The prevalence of patients with an inadequate immunological response was 29.6%. The percentage of non-AIDS diseases such as hypertension, cardiovascular disease (CVD), diabetes, tumor, and chronic kidney disease (CKD) was 32.9, 9.9, 31, 4.1, and 13%, respectively. In addition to baseline CD4+ T cell counts, CVD and tumor were associated with poor immune reconstitution in aged Chinese HIV-1 infected patients. The adjusted odds ratios (95% confidence interval) were AOR 2.45 (95% CI: 1.22–4.93) and 3.06 (95% CI: 1.09–8.56, p = 0.03). Inadequate immunological response was associated with greater mortality (AOR: 2.83, 95% CI: 1.42–5.67, p = 0.003) in this cohort. Conclusion These results tend to demonstrate appropriate drug selection at ART initiation and prevention of non-AIDS complications during ART decreased mortality of and an inadequate immunological response in aged HIV infected patients.